The Ventral and Dorsal Default Mode Networks Are Dissociably Modulated by the Vividness and Valence of Imagined Events - Lee, Sangil (J Neurosci, 2021)
Recent work has shown that the brain’s default mode network (DMN) is active when people imagine the future. Here, we test in human participants (both sexes) whether future imagination can be decomposed into two dissociable psychological processes linked to different subcomponents of the DMN. While measuring brain activity with fMRI as subjects imagine future events, we manipulate the vividness of these events to modulate the demands for event construction, and we manipulate the valence of these events to modulate the demands for event evaluation. We found that one subcomponent of the DMN, the ventral DMN or medial temporal lobe (MTL) subsystem, responds to the vividness but not the valence of imagined events. In contrast, another subcomponent, the dorsal or core DMN, responds to the valence but not the vividness of imagined events. This separate modifiability of different subcomponents of the DMN by vividness and valence provides strong evidence for a neurocognitive dissociation between (1) the construction of novel, imagined events from individual components from memory and (2) the evaluation of these constructed events as desirable or undesirable.